Violencia de género en Brasil y Cuba poesía contemporánea como resistencia - Christina Bielinski Ramalho (Revista Odisséia, 2022)
The book Sin mordaza, organized by Caridad Atencio and Christina Ramalho, presents poems by 33 Brazilian and Cuban poets through which the power of resistance represented by female authorship can be recognized in times of increasingly alarming rates of practices socially recognized as “gender violence”. Our proposal is, based on references such as Yanetsy Pino Reina, Ailynn Torres Santana, Amalia Pérez Martín, Diana Marcela Gómez Correal, Natalia Quiroga Díaz and María Lugones, among others, to undertake a sociocritical approach to some of these poems, in search of better understand the counter discursive marks present in these poems and the aspects that allow us to consider them also as signs of decoloniality since the patriarchy that sustained both experiences as colonized countries still shows its strength today.